PENGELOLAAN PERPUSTAKAAN BAITUL HIKMAH - Sudiar, Nining (Universitas Lancang Kuning, 2014)
Baitul Hikmah Library had been the peak of the advancement of knowledge for 508 year. It was the center of academy, translating, book publishing, discussing and the center qf stars observing. The book collections were also various. The arrangement and management of the collections were done very well because this library s building consisted of rooms and collections arranged based on their kinds and types. Besides, it had binded catalogue. The personnels of the library consisted of the director, translators, supervision editors, librarians, teaching staff, scientists, assistants, porter, and book,